Dehydrodiisoeugenol targets the PLK1-p53 axis to inhibit breast cancer cell cycle - Li, Lin; Zheng, Yifan; Yang, Yongxia; Shi, Senlin; Liu, Shangjie; Huang, Keying; Qiu, Luonan; Zhang, Rongxin; Huang, Wenbin; Leng, Yin (Frontiers in Pharmacology, 2025)
IntroductionThere are about 2,300,000 new cases of breast cancer worldwide each year. Breast cancer has become the first most common cancer in the world and the leading cause of death among women. At the same time, chemotherapy resistance in patients with advanced breast cancer is still a serious challenge. Alpinia Katsumadai Hayata (AKH), as a traditional Chinese herbal medicine, has a wide range of pharmacological activities. Related studies have found that many compounds in AKH have anti-breast cancer activity. However, it is still worth exploring which component is the main active component of AKH in inhibiting breast cancer and its mechanism of action.MethodsIn this study, dehydrodiisoeugenol (DHIE) was screened as the main active ingredient of AKH against breast cancer based on LC-MS combined with drug similarity and disease enrichment analysis. WGCNA, network pharmacology, molecular docking, transcriptome sequencing analysis, immune infiltration analysis and single-cell sequencing were used to explore the mechanism of DHIE on breast cancer. CCK-8, flow cytometry and Western blot were used to verify the results in vitro. The efficacy of the drugs was verified in vivo by constructing a subcutaneous tumor-bearing mouse model.ResultsOur research showed that DHIE and breast cancer enriched core gene targets mainly act on epithelial cells in breast cancer tissues and significantly inhibit the growth of breast cancer by affecting the PLK1-p53 signaling axis to arrest the breast cancer cell cycle at G0/G1 phase. Further analysis showed that although DHIE had opposite regulatory effects on different isoforms of p53 in different types of breast cancer cells, they eventually caused cell cycle arrest. In addition, in vivo studies showed that DHIE reduced tumor burden, significantly reduced the infiltration level of tumor proliferation-related marker Ki-67, and inhibited the expression of PLK1 in the mouse model, which was further enhanced when combined with DOX.DiscussionCollectively, our study suggests that DHIE in AHK may eventually induce cell cycle arrest and inhibit breast cancer growth by regulating the PLK1-p53 signaling axis, which may provide a new therapeutic strategy for breast cancer. However, the specific mechanisms by which DHIE regulates p53 in different subtypes of breast cancer and the advantages of chemotherapeutic combinations compared with other drugs are still worth exploring.